Ethnic and religious nationalism in Turkey: the cases of Atsız and Arvasi. (1st January 2023) - Yıldız, Tunahan; Kizir, Didem
ABSTRACT: This article compares the ideas of Hüseyin Nihal Atsız and Seyyid Ahmet Arvasi, two iconic ideologues of ethnic and religious nationalism in Turkey, respectively, on the issues of history, identity, and national ideal. It first argues that Atsız mainly presents a history of Turkish supremacism whereas Arvasi embraces a method of Islamization to remember history. It also demonstrates that Atsız tends to equate the racial and the national while Arvasi uses Islamic legitimacy for Turkish identity and nationalism. It is also evident that while Atsız offers classical pan-nationalism, Arvasi shows third-worldist and universalistic tendencies in defining Turkish destiny.